LITERATURE REVIEW: FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMSI FAST FOOD PADA REMAJA - Alfia Khoirunnisa; Nina Pamela Sari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research is a literature review aimed at examining the factors influencing fast food eating habits among adolescents. Articles were collected from databases such as Google Scholar, PubMed, and ScienceDirect, with a publication period between 2021 and 2025. Ten articles that met the criteria were then analyzed using a narrative synthesis method. The research findings reveal that fast food consumption habits are influenced by personal factors (such as knowledge, attitudes, self-control, and nutritional status), social factors (including peer influence, family support, and pocket money), as well as environmental factors like easy access, taste, and cost. Furthermore, exposure to social media and digital marketing has proven to increase adolescents' interest in fast food. This study concludes that adolescents' eating patterns are shaped by the interaction between internal and external elements, so prevention efforts must be carried out comprehensively